Interior Design of Rooms for Early Detection of Children’s Growth and Development (Case Study: Puskesmas Lawang) - Debri Haryndia Putri (Jurnal VOK@SINDO, 2013)
A child needs to be prepared for well-qualified human resources in the future. Regarding this, there are three basic needs for children to grow optimally: physical, emotional and educational needs. Puskesmas Lawang conducts an event of stimulation and early detection of children’s growth as an effort to fulfill children’s physical needs. However, the condition of facilities as well as building of Puskesmas often makes scared which finally obstructs the examination process. The research method used to solve this problem consists of three stages. The first stage is primary and secondary data collection. Those two kinds of data were compared and analyzed by using data tabulation method to get basic concept for detection room design. This concept was then used as the standard in designing the interior of the room for early detection of children’s growth. Based on the analysis of the activities, detection room is classified into 4 rooms: detection room for age 0-3-6-9-12 months, detection room for age 15-18-21-24 months, detection room for age 30-36-42-48 months, and detection room for age 54-60-66-72 months. In order to create friendly atmosphere in the examination room, the interior for each room is based on simulation activities according to Book of Detection Instrument as well as psychological characters of children within those particular ages.